Hungarian Monitoring, 1 February 1990 . [Magyar rádiófigyelő], 1990. február 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - President Bush's statement on American troop reductions - Members of pro-Solidarity Polish journalists' association demand purges - Modrow's statement on German re-unification - Bulgarian CP congress - Czechoslovakia: more salvos fired against Gabčíkovo-Nagymaros dam - Romania: National Salvation Front splits in two, trial of former communists continue Domestic Affairs: - Parliament: modifying the electoral law, property declarations - Open Skies conference - Hungarian politicians in New York - Pozsgay in Israel - Soviet troop withdrawals - Election: Alliance of Young Democrats (Fidesz) press conference, election programs Külpolitika: - Bush elnök bejelentése az amerikai csapatcsökkentésről - Tisztogatást követelnek a Szolidaritás-párti lengyel újságíró szövetség tagjai - Modrow nyilatkozata a német egyesítésről - A bolgár kommunista párt kongresszusa - Csehszlovákia: újabb össztűz a bősi vízlépcső ellen - Románia: kettészakadt a NMF, négyek pere Belpolitika: - Országgyűlés: választási törvény módosítása; vagyonnyilatkozat - Nyitott Égbolt tanácskozás - Magyar politikusok New Yorkban - Pozsgay Imre Izraelben - Szovjet csapatkivonás - Választás: FIDESZ sajtótájékoztató, választási műsorok